Qualitative study of the impact of early marriage (reproductive and psychological) on adolescent females - Haerani, Haerani; Tenriwati (Jurnal Konseling dan Pendidikan, 2025)
Indonesia occupies 37th place with amount wedding early the highest in the world and 2nd in Southeast Asia. Marriage dispensation data in Bulukumba Regency in 2021 amounted to 201 cases married teenagers early and Ujung Bulu District is Subdistrict with amount wedding early highest from 10 Sub-districts in Bulukumba namely totaling 19 teenagers spread across several sub-district. Marriage early is the marriage that was carried out before age reproduction, under 20 years For women and under 25 years old For men (BKKBN, 2018 in (nur asjeti, 2021) ). There are several factors that cause wedding early that is pregnant out of wedlock, arranged marriage, level low education, etc. Researchers interested do study This Because wedding early can cause various impact. For explore impact from aspect perceived health (reproductive and psychological) or experienced teenager the princess who has Marry early in the Ujung Bulu District, Bulukumba Regency. This study uses design study qualitative with approach phenomenology. 5 participants chosen in accordance criteria and recorded moment interview deep use guidelines interview not structured Then made transcript interview, next analyzed use Creswell model data analysis. Research result identify three theme main, namely : (1) meaning wedding early for teenagers, (2) reasons teenager choose For Marry early, (3) impact wedding early in adolescence. There are 3 themes found in study this and in it there is impact reproductive, psychological and educational. For teenagers princess to be more active and avoid things negative . It is hoped that more selective in choose Friend For socialize. More open with parents about all problems experienced For avoid socializing free and even pregnancy out of wedlock.